Flexible and insulating silicone rubber composites with sandwich structure for thermal management and electromagnetic interference shielding. (1st March 2022) - Guo, Yongqiang; Qiu, Hua; Ruan, Kunpeng; Wang, Shuangshuang; Zhang, Yali; Gu, Junwei
Abstract: High integration development of electronics requires materials possessing excellent thermal conductivity, electromagnetic interference (EMI) shielding, and electrical insulation. In this work, Fe2 O3 particles are deposited on carbon fibers (CF) and then utilized as fillers (CF@Fe2 O3 ) in boron nitride/silicone rubber (BN/SR) to fabricate sandwich structured CF@Fe2 O3 /(BN/SR) composites, herein, BN/SR as top & substrate layer, and CF@Fe2 O3 as middle layer. Orientation of BN in CF@Fe2 O3 /(BN/SR) composites realizes excellent in-plane thermal conductivity coefficient ( λ ∥ ), and the core-sheath structure of CF@Fe2 O3 achieves good EMI shielding performance by the "absorption-reflection (transmittance)-reabsorption" process of electromagnetic waves, insulation modification of CF and the sandwich structure strengthen the electrical insulation. When the amount of BN and CF@Fe2 O3 are 20.6 wt% and 45.5 wt%, respectively, the λ ∥, EMI shielding effectiveness, volume resistance and breakdown strength of CF@Fe2 O3 /(BN/SR) composites reach 3.86 W/(m·K), 37.7 dB, 6.2 × 10 14 Ω cm and 26.8 kV/mm, respectively, which are all higher than those of commonly fabricated CF/(BN/SR) composites with same amount of BN and CF (3.83 W/(m·K), 19.4 dB, 8.6 × 10 13 Ω cm and 21.4 kV/mm). CF@Fe2 O3 /(BN/SR) composites possess better cooling effect (5.6 °C) than that of commercial silicon grease (QM850) on the testing platform of computer's central processing unit, whose functions are more abundant and have wide application prospects in electronics. Graphical abstract: Image 1 Highlights: Designing core-sheath CF@Fe2 O3 to enhance electromagnetic interference (EMI) shielding and reduce electrical conductivity of carbon fiber (CF). Realizing orientation of boron nitride to enhance the in-plane thermal conductivity. Silicone rubber composites possess excellent thermal conductivity, EMI shielding and insulating performances.